Dairy bacteria remove in vitro dietary lectins with toxic effects on colonic cells - Zarate, Gabriela del Valle (2009)
Aims: To assess in vitro the ability of some dairy bacteria to bind concanavalin A (Con A), peanut agglutinin (PNA) and jacalin (AIL), preventing their toxicity on mouse intestinal epithelial cells (IEC). Methods and Results: Con A and AIL reduced significantly IEC viability in vitro, as determined by Trypan Blue dye exclusion or by propidium iodide/fluorescein diacetate/Hoescht staining. Different strains of dairy bacteria were able to remove lectins from the media. Two strains were subjected to treatments used to remove S-layer, cell wall proteins, polysaccharides and lectin-like adhesins. They were then assayed for the ability to bind dietary lectins and reduce toxicity against IEC and to adhere to IEC after interaction with lectins. Con A and AIL were removed by Propionibacterium acidipropionici and Propionibacterium freudenreichii by binding with specific sugar moieties on the bacterial surface. Removal of lectins by bacteria impaired IEC protection. Adhesion of P. acidipropionici to IEC was reduced but not abolished after binding Con A or AIL. Conclusions: Removal of Con A or AIL by dairy propionibacteria was effective to avoid the toxic effect against colonic cells in vitro. Significance and Impact of the Study: Consumption of foods containing these bacteria would be a tool to protect the intestinal epithelia.